Psyren. 5, Visions - Iwashiro, Toshiaki, 1977- (Shonen Jump, 2012)
After they see a video recording from the future that shows several of them being killed, Ageha and his friends search for a way to escape Sakurako and the other W.I.S.E. agents and avoid this dark fate.